Organic matter composition and thermal stability influence greenhouse gases production in subtropical peatland under different vegetation types. Issue 11 (November 2022) - Akinbi, G.O.; Ngatia, L.W.; Grace, J.M.; Fu, R.; Tan, C.; Olaborode, S.O.; Abichou, T.; Taylor, R.W.
Abstract: Peatlands are a major carbon (C) sink globally. Organic matter quality influence greenhouse gases production. However, little is known about how organic matter from different vegetation types, influences C composition and resultant greenhouse gases production in subtropical peatland. Anoxic incubation experiments were conducted using two types of peats with different botanical origin to assess C composition, CO2 and CH4 production. First peat had cypress dominance and the second knotted spikerush and water lily (spike + lily). Solid-state CPMAS 13 C NMR determined C chemical stability, MESTA determined C thermal stability, stable isotopes for C source and gas chromatograph for carbon dioxide (CO2 ) and methane (CH4 ). The results indicated dominance of autochthonous C as indicated by δ 13 C signatures. Low thermal stable C (LTSC) dominated in litter, FL (fermentation layer) and spike + lily sediment, high thermal stable C was dominant in cypress peat. O-alkyl C strongly correlated with LTSC whereas aromatic C correlated negatively with R400 (LTSC:total C ratio). Generally, O-alkyl decreased and alkyl increased along litter-FL-peat continuum. Spike + lily peat exhibited initial stage of decomposition. Indicated by increased alkyl C, aromatic C and aromatic:O-alkyl ratio with increasing peat depth. Also, exhibited 3 times more CH4 and CO2 production compared to cypress peat that dominantly exhibited second stage of decomposition. O-alkyl C exhibited positive relationship with CH4 ( P = 0.012, r 2 = 0.57) and CO2 ( P = 0.047, r 2 = 0.41) production whereas R400 related positively with CH4 ( P = 0.05, r 2 = 0.40). Organic matter thermal and chemical composition varied between the peat types and thermally and chemically labile C influenced CO2 and CH4 production. Abstract : Carbon composition; Carbon dioxide; Fermentation layer; Litter; Methane; Peat; Thermal stability; Vegetation types.